RFID-based Drug Management and Monitoring System, Case of Public Hospitals in Tanzania, A Review Paper - Prisila Ishabakaki; Shubi Kaijage (Computer Engineering and Applications Journal, 2015)
Radio frequency Identification (RFID) is an automatic identification technology that enables tracking of people and objects. Recently, RFID technology has been deployed in hospital environment for patient and equipment tracking, surgical equipment monitoring, medication monitoring and improving health record access in emergency cases. The main advantages RFID technology are to provide resource optimization, quality customers’ care, enhanced accuracy, efficient and effective business processes and healthcare processes. The pharmacy department undergoes challenges such as complex manual work of record keeping and inventory management. The RFID technology can be deployed in pharmacy hospital unit to automate pharmacy process. In this work we present a review on current pharmacy management practices in the case study of public hospital in Tanzania, review on different research work to address the pharmacy challenges and finally proposed a system to overcome the limitation identified in the current systems.